2007
DOI: 10.1091/mbc.e07-06-0581
|View full text |Cite
|
Sign up to set email alerts
|

A Single MAPKKK Regulates the Hog1 MAPK Pathway in the Pathogenic FungusCandida albicans

Abstract: The Hog1 mitogen-activated protein kinase (MAPK) plays a central role in stress responses in the human pathogen Candida albicans. Here, we have investigated the MAPK kinase kinase (MAPKKK)-dependent regulation of the pathway. In contrast to the Hog1 pathway in Saccharomyces cerevisiae, which is regulated by three MAPKKKs (Ssk2, Ssk22, and Ste11), our results demonstrate that Hog1 in C. albicans is regulated by a single MAPKKK Ssk2. Deletion of SSK2 results in comparable stress and morphological phenotypes exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
123
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 56 publications
(93 reference statements)
4
123
0
1
Order By: Relevance
“…In C. albicans, deletion of SSK2, but not STE11, generates phenotypes highly comparable to those of pbs2⌬ and hog1⌬ mutants in stress response and morphology and completely abolishes phosphorylation and nuclear accumulation of Hog1 in response to external stress (33). Notably, the ssk2⌬ mutant exhibits constitutively filamentous morphology, like the hog1⌬ mutant, with increased expression of hypha-specific genes such as HWP1 and ECE1, while the ssk1⌬ mutant is almost completely defective in hyphal formation (33). This indicates that Ssk2 is negatively regulated by either Ssk1 or other, unknown, signaling components for controlling the morphological differentiation of C. albicans.…”
Section: The Hog1 Mapk Modulementioning
confidence: 92%
See 3 more Smart Citations
“…In C. albicans, deletion of SSK2, but not STE11, generates phenotypes highly comparable to those of pbs2⌬ and hog1⌬ mutants in stress response and morphology and completely abolishes phosphorylation and nuclear accumulation of Hog1 in response to external stress (33). Notably, the ssk2⌬ mutant exhibits constitutively filamentous morphology, like the hog1⌬ mutant, with increased expression of hypha-specific genes such as HWP1 and ECE1, while the ssk1⌬ mutant is almost completely defective in hyphal formation (33). This indicates that Ssk2 is negatively regulated by either Ssk1 or other, unknown, signaling components for controlling the morphological differentiation of C. albicans.…”
Section: The Hog1 Mapk Modulementioning
confidence: 92%
“…In addition, sexual differentiation under nitrogen starva- In contrast to the model yeasts, most fungal pathogens appear to contain a single Ssk2-like MAPKKK. Two recent studies showed that a single MAPKKK is sufficient to control the Pbs2-Hog1 signaling pathway in C. albicans and C. neoformans (12,33). In C. albicans, deletion of SSK2, but not STE11, generates phenotypes highly comparable to those of pbs2⌬ and hog1⌬ mutants in stress response and morphology and completely abolishes phosphorylation and nuclear accumulation of Hog1 in response to external stress (33).…”
Section: The Hog1 Mapk Modulementioning
confidence: 99%
See 2 more Smart Citations
“…Similar to MAPKs, SAPKs are activated through a series of upstream events to induce the expression of stress-protective genes and coordinate diverse cellular processes that confer stress resistance (Kyriakis & Avruch, 2001). The SAPK modules that are present in fungal species are remarkably conserved in mammals ( Figure 2B): Win1/ Wis4-Wis1-Sty1 (S. pombe) (Millar et al, 1995;Samejima et al, 1997;Shieh et al, 1997a), SSK2/22-PBS2-HOG1 (S. cerevisiae) (Brewster et al, 1993;Posas & Saito, 1998;Posas et al, 1996), SskB-PbsB-HogA (A. nidulans) (Aguirre et al, 2005;Kawasaki et al, 2002;Vargas-Pérez et al, 2007), Ssk2-Pbs2-Hog1 (C. albicans) (Cheetham et al, 2007;San José et al, 1996) and MTK1/ASK1/TAK1/MLKs/MEKKsMKKs-p38 (a, b, g, d) (mammals) (Mielke & Herdegen, 2000;Nebreda & Porras, 2000;Paul et al, 1997;Tibbles & Woodgett, 1999). Among other TFs, the mammalian p38 SAPK pathway regulates ATF2, which is the ortholog of the fission yeast Atf1 TF (Table 1 and Figure 2B) (Dérijard et al, 1994).…”
Section: Stress Signaling Pathways: the Central Role Of The Mapk Familymentioning
confidence: 99%